The church and the street: Copts and interest representation from Mubarak to Sisi. Issue 5 (19th October 2020) - Rowe, Paul S.
ABSTRACT: The Arab Spring ushered in by the revolutions of early 2011 mobilised numerous communities against the authoritarian governments of the Middle East. For Egyptian Christians, known as Copts, participation in the protests that deposed Hosni Mubarak represented not just a challenge to the government, but to the Coptic Orthodox Church that had sided with the regime for more than two decades. The successful protests marked the victory of the street over the regime, and a challenge for the traditional Church leadership. Over the next two years, lay initiatives challenged the special role of the Church while Egypt experimented with democracy. However, ultimately the various challenges of Islamist majoritarianism, the power of the military, and internal divisions in the community demonstrated the enduring power of the Coptic Orthodox Church as the representative of Coptic interests. The restoration of military dominance solidified the neo-millet alliance between the Church and the regime. The current military regime has increased its repression of rival poles of authority. At the same time, the Coptic Orthodox Church has deepened its own efforts to control Coptic representation. Coptic interest representation in the age of Sisi represents a parallel triumph of the barracks and the Church over the streets.